Peran brand ambassador, brand love, dan kualitas produk terhadap keputusan pembelian skincare skintific pada mahasiswa S1 universitas dian nuswantoro semarang - Sarah Nurrohamah; Handy Nur Cahya; Vincent Didiek Wiet Aryanto; Amalia Nur Chasanah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Awareness regarding the importance of skin health makes people care and look for the best care products. Skintific has emerged as a brand that is much loved by the public and has a wide market. To determine the influence of Brand Ambassador, Brand Love, and Skintific Product Quality on purchasing decisions among students at Dian Nuswantoro University, Semarang. Quantitative Data, analysis using Smart-PLS. The research sample was 154 respondents using Purposive sampling. Results: H1 is rejected, namely Brand Ambassador does not influence Purchasing Decisions with a p value of 0.972, H2 is accepted, namely Brand love has a positive effect on Purchasing Decisions with a p value of 0.001, H3 is accepted, namely Product quality has a positive effect on Purchasing Decisions with a p value of 0.001, H4 is accepted, namely Brand Ambassador, Brand love, and Product Quality simultaneously have a positive and significant effect on Purchasing Decisions by 61.6%. Conclusion: Brand Ambassador does not affect Purchasing Decision; Brand love has a positive effect on Purchasing Decision; Product quality has a positive effect on Purchasing Decision; Brand Ambassador, Brand love, and Product Quality simultaneously have a positive and significant effect on Purchasing Decision